Green Banking Awareness and Its Influence on Customer Decision-Making in Jaipur’s Banking Sector - Meena, Pooja; Jangid, Kamal Kishor (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Green banking is a main tool used to support environmentally friendly actions within the financial business. The research examines how the knowledge of green banking influences customer actions in the city’s banking sector. Using a combination of questionnaires and interviews with customers, data were gathered from 100 bank users who work in both public and private organizations. The outcome shows that customers who are informed about green banking tend to prefer eco-friendly banking services. Also, becoming more environmentally aware, using online banking and going paperless were important factors driving what customers choose. In brief, the study finds that more people accessing green banking services are more likely to make greener banking choices.